Axial compressive behavior of CFRP confined rectangular CFT columns using high-strength materials: Numerical analysis and carrying capacity model. (February 2022) - Du, Yansheng; Fu, Mingxuan; Chen, Zhihua; Yan, Jia-Bao; Zheng, Zihan
Abstract: The concrete-filled steel tubular columns using high-strength steel and concrete have the advantages of high strength and small cross-section. However, the rectangular concrete-filled steel tubular (RCFT) columns using high-strength materials are susceptible to local buckling and lower ductility. The experimental study on the axial compression behavior of FRP confined concrete-filled steel tubular columns using high-strength materials show that FRP could restrain the deformation of steel tube and concrete and delay the local buckling of steel tube effectively. Based on the experimental study, the finite element model of FRP confined RCFT columns was established and verified by comparing the carrying capacity and load-displacement curves of test including ten specimens. Parametric analysis considering the corner radius, number of FRP layers, width-to-thickness ratio, concrete strength and aspect ratio is conducted to analyze the influence of different parameters on the axial compressive performance. Through the analysis of test and parametric data, theoretical model and method to design the axial capacity of the FRP confined RCFT columns are proposed. The theoretical models and methods could accurately predict ultimate carrying capacity of FRP-RCFT columns under axial compression and provided theoretical support for the application of FRP confined concrete-filled steel tubular columns using high-strength materials.